Dyeing of Mulberry Silk Using Binary Combination of Henna Leaves and Monkey Jack Bark. Issue 2 (1st February 2021) - Boruah, Gitanjali; Phukan, Ava Rani; Kalita, Binita Baishya; Pandit, Pintu; Jose, Seiko
ABSTRACT: The present work deals with the dyeing of mulberry silk yarns with a mixture of two colorants extracted from Lawsonia inermis and Artocarpus lacucha . The dyes were extracted with acid, alkaline and neutral medium. Different proportions of the dye and metallic mordants were made and the dyeing was performed at 80°C with pre, post and meta mordanting techniques. The extent of dyeing was studied on the basis of K/S values. It was found that, the highest dye intensity was obtained when a mild alkaline medium was used for dye extraction. The highest color value was obseved for the combination of monkey jack dye mordanted with copper sulfate by the meta mordanting method. The color fastness properties were also found to be good. The phytochemical analysis of the selected dyes showed the presence of active components like saponins, glycosides, terpenoids and tannins, which was further confirmed by Fourier Transform Infrared Spectroscopy.